Association between perceived stress and history of intimate partner violence throughout life and during the COVID-19 pandemic - da Costa Siqueira, Loys Lene; de Melo Batista, Karla; Marabotti Costa Leite, Franciéle (Frontiers in Public Health, 2023)
Introduction Intimate Partner Violence (IPV) is a significant public health issue, characterized by being a highly stressful experience for its victims. The relationship between IPV and stress creates a harmful cycle with broad health implications, affecting individuals and society at large. Despite its significance, there's a noticeable lack of research on this topic, especially regarding IPV throughout one's life and during the pandemic. Objective To verify the association between perceived stress and the history of intimate partner violence throughout life and during the COVID-19 pandemic. Materials and methods Analytical cross-sectional epidemiological study with a sample of 1,086 women. Sociodemographic information and violence history, assessed using the World Health Organization Violence Against Women (WHO VAW STUDY), along with perceived stress measured by the short version of the Perceived Stress Scale (PSS), were collected. The sampling process unfolded through multiple stages. For bivariate analyses, the t-test and ANOVA were performed, whereas for multivariate analyses simple and multiple linear regression were performed. The software Stata® version 15.1 and R® were used. Results Women who reported having suffered intimate partner violence throughout their lives had higher means of stress (18.49), with an average increase of 4 points without adjustments and 3.5 points after adjustments for sociodemographic variables. Similarly, during the COVID-19 pandemic (19.01), stress increased by an average of 3.3 points, which was reduced to 2.8 points after adjustments. Conclusion The results indicate an association between intimate partner violence and an increase in women's perceived stress, both throughout life and during the pandemic. The importance of preventive approaches, promoting gender equality and preventing IPV from the early stages of life is highlighted. In addition, they underscore the urgency of evidence-based interventions of a comprehensive nature to deal with this complex issue in a careful and effective manner. The cross-sectional nature of this study limits the inference of causality, and an additional limitation is acknowledged concerning information bias. This bias relates to the multifaceted issues surrounding the concept of violence, potentially influencing the accuracy of participants' information and complicating the measurement of violence.